DETERMINATION THE MECHANICAL COMPOSITION OF THE GRAPEBUNCH AND BUNCHES OF LOCAL GRAPE VARIETIES AND SELECTING GOOD VARIETIES - Nafosat Djonibekova; Sukhrob Robbimov (Galaxy International Interdisciplinary Research Journal, 2025)
In this article, the grape varieties, grapebunch weight, size, number of bunches, petiole, skin, juice, and fruit percentage were determined, and the highest grapebunch weight was determined in the varieties Katta Kurgan (445 g), Oktyabrsky (470 g), Sultani (600 g), Muscat Uzbekistansky (550 g), Khusayne Kelin Barmoq (478 g). The largest grape heads were recorded in the Andijansky Chorny, Rizamat, and Muscat Uzbekistansky varieties. The Andijansky Chorny, Djanjal Kara, Doroi, Nimrang, Perlet, and Rizamat varieties with the lowest percentage of bunch to the total grape head weight were distinguished. Among the grape varieties, the highest juice yield to the total grape head weight was determined in the Oktyabrsky, Ranniy Shroedera, Soyaki, Khusayne Muskatny, and Ertapishar varieties. Among the grape collection, differences in seed size and size were found among different varieties.